Modern Challenges of the United States Emergency Medical Care System: Interrelated Concerns with Multiple Causes - Yusuf, Raffi Ahmed (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7664 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):10-17